2011
DOI: 10.4103/0019-5413.83762
|View full text |Cite
|
Sign up to set email alerts
|

Internal fixation of fractures of both bones forearm: Comparison of locked compression and limited contact dynamic compression plate

Abstract: Background:The locking compression plate (LCP) with combination holes is a newer device in fracture fixation. We undertook a study comparing the LCP with limited contact dynamic compression plate (LC-DCP) in the treatment of diaphyseal fractures of both bones of the forearm.Materials and Methods:This is a prospective comparative study, 36 patients (18 in each group) with fractures of both the forearm bones (72 fractures) were treated with one of the two devices. The average age of the patients was 30.5 years (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
73
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(88 citation statements)
references
References 20 publications
12
73
2
1
Order By: Relevance
“…9 More recently, Saika et al too have reported 100% union rates with mean time to union lesser with LCP than LC-DCP. 24 Matching observations were published by Azboy et al using DCP in place of LC-DCP. 25 On the contrary, Stevens et al proclaimed mean consolidation time favoring DCP over LCP.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…9 More recently, Saika et al too have reported 100% union rates with mean time to union lesser with LCP than LC-DCP. 24 Matching observations were published by Azboy et al using DCP in place of LC-DCP. 25 On the contrary, Stevens et al proclaimed mean consolidation time favoring DCP over LCP.…”
Section: Discussionsupporting
confidence: 62%
“…This was in sharp contradiction to Saikia and Haribabu et al who recorded it to be more with LCP although insignificantly. 24,31 No significant differences could be brought about between the group with regard to functional aspects in spite of exercising on three different criteria (ROM: elbow and wrist flexion and forearm pronation and supination; Andersons criteria and DASH score). Many precedent studies too have echoed our findings.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The authors concluded that the LCP and LC-DCP provided similar results. [11] In 32 patients (45 fractures) with forearm fractures who were treated with LCPs, Leung and Chow [14] reported that union was achieved at an average of 20 weeks. However, they encountered delayed union in 2 (6.3%) cases.…”
Section: Imad World Journal Of Pharmaceutical Researchmentioning
confidence: 99%